HUBUNGAN LINGKUNGAN KERJA, KREATIVITAS DAN KINERJA KARYAWAN SERTA PERAN MODERASI KARAKTERISTIK INDIVIDU (STUDI PADA KSU GANGGA MULYA JEMBRANA) - I Wayan Guntur Mahardika; M. Jamal Abdul Nasri; Djuni Farhan (Journal of Innovation Research and Knowledge, 2026)
This study aims to analyze the influence of the work environment on employee performance, with creativity as a mediating variable and individual characteristics as a moderating variable at KSU Gangga Mulia, Jembrana. The research method used is quantitative with an explanatory design. The research population involved all 38 employees of KSU Gangga Mulia, utilizing a saturated sampling (census) technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) via SmartPLS software. The results showed that: (1) Work environment does not have a direct significant effect on employee performance; (2) Work environment has a significant effect on creativity; (3) Creativity has a significant effect on performance; (4) Individual characteristics have a significant effect on performance; (5) Creativity acts as a full mediator in the relationship between work environment and performance; (6) Individual characteristics do not moderate the relationship between work environment and performance; (7) Individual characteristics significantly moderate (strengthen) the influence of work environment on creativity; and (8) Individual characteristics significantly moderate (strengthen) the influence of creativity on performance. These findings emphasize that internal factors such as creativity and personal character are the primary keys to converting work environment conditions into tangible performance achievements.